Re‐esterified oils from palm acid oil do not alter pork fatty acid composition. Issue 9 (24th August 2015) - Tres, Alba; Muzofa, Farayi Martin; Vilarrasa, Ester; Guardiola, Francesc; Codony, Rafael
<x xml:space="preserve">Abstract</x> New fat products have been developed by chemically re‐esterifying acid oils (a by‐product of the food oil refining industry) with glycerol (a by‐product from biodiesel industry). These new products show lower free fatty acid content than acid oils and a fatty acid distribution within the positions of acylglycerols different from that of native oils. In this paper, we aim at assessing if the unique composition of re‐esterified palm oils (compared to native and acid oils) would affect pork and back fat fatty acid composition. A total of 24 pigs were fed one of the four experimental diets containing 4% experimental fat: native palm oil (PN), palm acid oil (PA), or two re‐esterified palm oils (PEL and PEH). Our results show that meat from pigs fed re‐esterified palm oils did not differ significantly in terms of total fatty acid and sn‐2 fatty acid compositions compared to PN or PA. Practical applications: Acid oils are by‐products of the food industry. They could be re‐utilized as feed ingredients but their free fatty acid content is usually high. High free fatty acid contents in diets have been related to low digestibility values when used in feed. New fat products have been developed by their chemical esterification with glycerol (a by‐product from biodiesel industry). Here, we have verified that these re‐esterified products would not alter pork fatty acid composition with respect to the use of native palm oil. Since results on productive parameters showed that they might increase feed efficiency and digestibility, overall the results support the re‐utilization of these fat by‐products in feed, alternative to the use of native palm oil or palm acid oil, provided that the benefits of the increase in feed efficiency counteract the cost of the esterification process. <inline-graphic xlink:href="ark:/27927/pgj2n17ws58" content-type="ejlt201400544-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> New fat products have been developed by chemically re‐esterifying palm acid oil (a by‐product of the palm oil refining industry) with glycerol. Compared to acid oils, they show a reduction of free fatty acids and an increase of partial acylglycerols. The fatty acid distribution within the positions of acylglycerols is different from that of native oils. This study has shown that their use in pig feed does not modify pork fatty acid composition compared to native or acid palm oil.